A Systematic Review of Literature on the Use of Extended Reality in Logistics and Supply Chain Management Education: Evolution of Research Themes and System-Level Trends - Xiaonan Zhu; Po-Lin Lai; Xinjie Li; Yaoyan Wang; Xi Pei (Systems)
Amid the digital transformation of logistics and supply chains, Extended Reality (XR) technologies have emerged as promising tools for enhancing education and training. However, existing studies are fragmented, often limited to case-specific applications with minimal theoretical or longitudinal depth. This study conducts a systematic literature review of 1172 publications from 2009 to December 2024, using PRISMA protocols and VOSviewer-based text mining to identify trends and research gaps. A total of 59 peer-reviewed articles were selected for in-depth analysis based on relevance, methodological transparency, and educational scope. Five key themes emerged: immersive instructional innovation, XR-enabled safety training in high-risk logistics environments, simulation-based development of practical competencies, intelligent learning environments with personalized features, and competency alignment with Industry 4.0. These themes span higher education, vocational training, and community-based learning. A temporal analysis reveals a three-phase evolution: exploratory (2009–2013), applied implementation (2016–2020), and integrative innovation (2021–2024). Despite increasing interest, the field remains dominated by descriptive methods and lacks systematic evaluation frameworks. XR shows strong potential to bridge the theory–practice gap and support scalable, interdisciplinary education models. Future research should prioritize evidence-based frameworks and cross-contextual validation to support the effective adoption of XR in LSCM education.